Investigating the Use of Information and Communication Technology in the Design of a Smart City in the 22nd District of Tehran (SWOT Analysis) - Ahmadi, Rana; ArianManesh, Soheil (International journal of industrial engineering and operational research, 2024)
Smart city is an emerging phenomenon in city development. It is used geographically for smartness in intelligent cities, using modern technologies and technologies such as the Internet of Things (IoT), artificial intelligence (AI), and information systems. These technologies lead to better and more efficient energy management, transportation, waste, and water resources. Urban resources help in intelligent cities. It also increases efficiency, reduces resource wastage, and improves the citizens' quality of life. The smart city collects comprehensive data and uses them to make optimal decisions. With the smartening of cities, citizens can effectively communicate with the urban environment. They will have easy and intelligent access to public services. Also, sustainable development, air pollution, traffic reduction, and urban safety improvement are other advantages of the smart city. The metropolitan population, the need for optimal management of resources, and the use of new technologies in the design and management of cities have become very important. This article examines the use of information and communication technology (ICT) in designing and implementing a smart city in the 22nd district of Tehran. Using new concepts and technologies, this area can become an intelligent city that optimizes resources and improves citizens' quality of life.